Current Approaches in Forensic Pathology Evaluation of Abusive Head Trauma - Ekemen, Süheyla; Pakiş, Işıl (The Bulletin of Legal Medicine, 2024)
Abusive head trauma is a serious type of child abuse that causes skull and brain damage as a result of the child being violently shaken and/ or exposed to blunt trauma. It is seen in children under 5 years, most commonly under 2 years. Its classic triad is the simultaneous occurrence of subdural hematoma, retinal hemorrhage, and encephalopathy. Histopathological and immunohistochemical examinations at autopsy are crucial in determining the cause of death and the age of the lesions in cases resulting in death. While these examinations confirm the macroscopic diagnosis, they also enable the determination of macroscopically undetectable findings and the age of the trauma. Determining a protocol specifically for central nervous system examinations in cases of suspected child abuse and sampling by this standard approach will make significant contributions to the proper functioning of justice.